Single-pixel camera - Tom A. Kuusela (AMER ASSOC PHYSICS TEACHERS, 2022)
A single-pixel camera is an interesting alternative to modern digital cameras featuring millions of pixels. A single-pixel camera is a method that produces images by exploring the object features with a series of spatially resolved patterns of light field while measuring the correlated intensity on a single detector. Nowadays, single-pixel cameras are used on those applications where multi-pixel detectors are not available because the wavelength is not in visible range or light intensity is extremely low. The spatial light modulator is an essential part of any single-pixel camera systems. They are, unfortunately, very expensive. We describe a low-cost version of single pixel camera that can be used in undergraduate physics laboratories. We show that with this camera setup students can easily demonstrate basic characteristics of computational ghost imaging and traditional raster and basis scan. Finally, we explain how to perform compressive sampling of images where the number of measurements is well below the actual pixel number. Compressive sampling is a rapidly expanding method to perform image or signal reconstructions in many field of research.